Correlations of p53, SLC7A11, and CD3+/CD8+ T cells with pathological features and prognosis in endometrial carcinoma - Lv, Yuanjie; Zhou, Weiwei; Zhang, Jingyu; Feng, Jing; Xing, Rongge; Miao, Zhigang (Journal of Medical Biochemistry, 2025)
Objective: This study investigates the clinical significance of SLC7A11, p53, and CD3+/CD8+ T cells in endometrial carcinoma (EC). By evaluating their expression patterns and correlations with histopathological parameters and patient outcomes, we aim to develop a prognostic risk model integrating these biomarkers. Methods: We enrolled 134 EC patients (observation group) diagnosed between February 2023 and January 2024 and 128 concurrent healthy controls. Quantitative and qualitative assessments were conducted to measure SLC7A11, p53, and CD3+/CD8+ T cell levels. Diagnostic performance of individual and combined markers was analyzed using receiver operating characteristic (ROC) curves, while a logistic regression-based predictive model was developed. Associations of these biomarkers with EC histopathological features and 1-year survival outcomes were further evaluated. Results: Compared to controls, EC patients exhibited notable reductions in CD3+/CD8+ T-cell infiltration but elevations in SLC7A11 and p53 expression (P<0.05). According to qualitative analysis, CD3 and CD8 positivity were similarly lower in tumor tissues than in adjacent normal tissue, whereas SLC7A11 and p53 staining were more frequent in malignant lesions (P<0.05). For EC diagnosis, the combined AUC of p53, SLC7A11, and CD3+/CD8+ T cells reached 0.883 (72.4% sensitivity, 88.3% specificity). Their combination also effectively predicted 1-year mortality risk (AUC = 0.889), with 82.4% sensitivity and 81.0% specificity. Conclusion: p53, SLC7A11, and CD3+/CD8+ T cells show intimate connections with EC. A diagnostic model incorporating these biomarkers enhances the accuracy of EC detection, offering improved clinical utility.